March: Book Two Book two - Lewis, John, 1940-2020; Aydin, Andrew; Powell, Nate; Ross, Chris; Top Shelf Productions (Comic Book Publisher); Small Press Expo Collection (Library of Congress) (Marietta, GA : Top Shelf Productions, 2015)
"After the success of the Nashville sit-in campaign, John Lewis is more committed than ever to changing the world through nonviolence -- but as he and his fellow Freedom Riders board a bus into the vicious heart of the deep south, they will be tested like never before."--page 3 of cover.
"Designed by Chris Ross and Nate Powell"--Colophon.
Book two of a graphic novel trilogy.
Young Adult.
850
Accelerated Reader
Keywords: Lewis, John, -- 1940-2020 -- Comic books, strips, etc; United States. -- Congress. -- House -- Biography -- Comic books, strips, etc; Student Nonviolent Coordinating Committee (U.S.) -- Biography -- Comic books, strips, etc; Legislators -- United States -- Biography -- Comic books, strips, etc; African American legislators -- Biography -- Comic books, strips, etc; African American civil rights workers -- Biography -- Comic books, strips, etc; Civil rights workers -- United States -- Biography -- Comic books, strips, etc; African Americans -- Civil rights -- Comic books, strips, etc; Civil rights movements -- Southern States -- History -- Comic books, strips, etc; Civil rights movements -- United States -- Comic books, strips, etc; Comic books, strips, etc; Comics (Graphic works); Biographical comic books; Graphic novels